An ectopic human XIST gene can induce chromosome inactivation in postdifferentiation human HT-1080 cells - Hall, Lisa L. (National Academy of Sciences, 2002)
It has been believed that XIST RNA requires a discrete window in early development to initiate the series of chromatin-remodeling events that form the heterochromatic inactive X chromosome. Here we investigate four adult male HT-1080 fibrosarcoma cell lines expressing ectopic human XIST and demonstrate that these postdifferentiation cells can undergo chromosomal inactivation outside of any normal developmental context. All four clonal lines inactivated the transgene-containing autosome to varying degrees and with variable stability. One clone in particular consistently localized the ectopic XIST RNA to a discrete chromosome territory that exhibited striking hallmarks of inactivation, including long-range transcriptional inactivation. Results suggest that some postdifferentiation cell lines are capable of de novo chromosomal inactivation; however, long-term retention of autosomal inactivation was less common, which suggests that autosomal inactivation may confer a selective disadvantage. These results have fundamental significance for understanding genomic programming in early development.